Changes In Ventilation Parameters For Various Types Of Prevmania - Boltaeva Mayram Miraliеvna (Indonesian Journal of Innovation Studies, 2022)
To study the importance of functional abnormalities of thyroid status in patients with community-acquired pneumonia, to recognize their clinical significance while choosing treatment tactics.